Aspects of the activity rhythm and population size of troglophilic mygalomorph spiders (Trechona sp., Dipluridae) in a quartzite cave in Minas Gerais, Brazil - Guadanucci, Jose Paulo L. [UNESP]; Braga, Pilar Louisy M.; Sa, Fernanda de S. (Taylor & Francis Ltd, 2015)
Records of mygalomorphs inhabiting caves have increased in the past years. We present data on a population of Trechona sp. spiders, found in a quartizite cave in Diamantina, Minas Gerais, Brazil. The spiders and their retreats were marked, and this population was followed for 17months. The population consisted of up to 100 individuals, comprising the worlds'largest known cave-dwelling population of mygalomophs. The estimated population size (Jolly-Seber model) varied from 50.36 to 853.43, the latter considered much overestimated. We did not find individuals of Trechona sp. in the surrounding epigean areas. The number of spiders was higher in the entrance zone than in the other two zones (twilight and dark zones). We found that individuals at the entrance zone showed similar activity to a nocturnal spider, whereas the other two groups showed conspicuous differences from this pattern, spending longer periods without rest, on the sheet-web as a sit-and-wait predator.
Keywords: Mygalomorphs; Circadian cycle; Sheet-web; Subterranean